(untitled) (Acta Entomológica Chilena, 2022)
Twospeciesof Pnonyx Van der Linden, 1827. P neoxenus (Kohl, 1890) and P nolonitidum (Willink, 1951), are cited for the First time at Magellan Región. Same taxonomic characlers and geographic dislribution are analized.